Net CO2 exchange in a rural area of the upper Spanish plateau - Sánchez, María Luisa; De Torre, Beatriz; Pérez, Isidro Alberto; García, María Ángeles (Física de la Tierra, 2008)
In 2004 we installed a CO2 eddy-correlation system at the CIBA centre located in an agriculture area in the geographical centre of the semi-arid upper Spanish plateau. 30-min Net Ecosystem Exchange measurements, NEE, were systematically performed from February to January 2005 (except in August). The period of study was dominated by drought, the yearly accumulated rainfall amounting to 300 mm. This paper presents the most relevant experimental results obtained, identifies the main driving factors governing NEE and assesses the influence of one of the most common vegetation indexes, the Normalized Difference Vegetation Index, NDVI, on gross primary production (GPP) in the growing season. The NDVI data used correspond to the MODIS 16-day composites. The results obtained show: 1) a marked seasonal variation featured by CO2 uptake during the growing season (March-June 16) and CO2 emissions from October to January. 2) low monthly NEE means ranging from 0.21 to -1.39 μmol/m2.s, 3) consistent diurnal cycles with their corresponding Photosynthetic Active Radiation, PAR, and vegetation cover evolution and 4) a satisfactory linear relationship of GPP versus MODIS 16-day NDVI during the growing season (R2=81.8%).